Adult learning : linking theory and practice - Merriam, Sharan B.; Bierema, Laura L. (Laura Lee), 1964- (San Francisco : Jossey-Bass, 2014)
"Solidly grounded in theory and research, but concise and practice-oriented, Adult Learning: Linking Theory and Practice is perfect for graduate students and practitioners alike. The expert authors have infused each chapter with teaching and instructional applications as well as personal relevance for the reader. The contents covers: Adult Learning in Today's World--globalization; technology; social networking; formal, non-formal, and informal learning The Culture and Context in Adult Learning The Foundations of Learning Theory--behaviorism, cognitive psychology, social constructivism, situated cognition Andragogy Self-directed Learning Transformative Learning The Body and Spirit in Learning Experience and Learning Motivation and Learning The Brain and Mind, including neuroscience Intelligence--practical and emotional intelligence, learning and cognitive styles Critical Thinking and Critical Perspectives "--
Includes bibliographical references and indexes.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2013. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Adult education; Adult education -- Research; Education and globalization; Activity programs in education; Electronic books